Pengaruh Suhu dan Lama Pengeringan terhadap Mutu Silase Limbah Pengolahan Kodok Beku (Rana sp.) yang Dikeringkan dengan Penambahan Dedak Padi - Rosidin Rosidin; Kiki Yuliati; Siti Hanggita R.J. (Universitas Sriwijaya, 2012)
The objectives of this study were to determine the effects of temperature and duration of drying on the quality the silage made from the waste of frozen frog (Rana sp.) processing with addition of rice bran. This research was designed using completely randomized factorial design with two treatments and two replications. The treatments were temperatures (40 oC and 50 oC) and durations of drying (20, 25, 30, 35, and 40 hours). The observed parameters include contents : bulk density, water, protein, fat, and crude fiber. The result showed that temperature and duration of drying affected significantly on bulk density, water content, and protein of the silage. Temperature and duration of drying had significant effect on fat content , but no significant differences in interaction between each other. Only the temperature treatment had significant effect on crude fiber. T2t5 (temperature of 50 oC and 40 hours of drying time) produced silage meal with lower water content (7.45 %), high protein content (59.63 %), fat content (8.50 %), crude fiber (12.65 %), and bulk density (0.620 g/mL). Keyword: Temperature, Duration of Drying, The Silage, Rice Bran